Assessment of DNA Damage of Oral Mucosa due to Ceramic Bracket Using Comet Assay and Mutagenicity of Orthodontic Bonding System Using Ames Test - Adham, Riaz; Ab Rahman, Norma; Ponnuraj, Kannan Thirumulu (UI Scholars Hub, 2023)
Objective: The objective of this study was to determine the DNA damage caused by ceramic bracket (Clear II, SIA Orthodontic Manufacturer Srl, Italy) on human buccal mucosal cells using comet assay and the mutagenicity of orthodontic bonding system (Transbond XT; 3M Unitek) by Ames test. Methods: In this study, twenty orthodontic patients were recruited from Specialist Orthodontic Clinic, Hospital Universiti Sains Malaysia. The Buccal mucosal cell sample was obtained from each patient at three time points-before (TO), after one month (T1) and after two months (T2) of ceramic bracket placement for performing comet assay. The spot test version of Ames test was performed using four Salmonella Typhimurium (S. Typhimurium) tester strains (TA 98, TA100, TA1535 and TA1537) for mutagenicity testing. Total comet score (TCS) and damage frequency (DF) were used to determine the DNA damage using non-parametric Friedman test followed by multiple pairwise comparison. The Ames test was analysed by a non-statistical method based on revertant growth ring formation. Results: There was no significant change of both TCS and DF between T0 and T1, but both parameters increased significantly from T0 to T1 and from T1 to T2. Non-statistical analysis was carried out to evaluate the results of Ames test based on the formation of revertant colony growth ring. None of the S. Typhimurium tester strains showed any revertant growth ring formation around the light cure adhesive primer. Conclusion: Ceramic bracket does not cause any DNA damage on human buccal mucosal cells and light cure adhesive primer is non mutagenic under the present test conditions.